Magnesium sulfate reduces EEG activity but is not neuroprotective after asphyxia in preterm fetal sheep. Issue 4 (April 2017) - Galinsky, Robert; Draghi, Vittoria; Wassink, Guido; Davidson, Joanne O; Drury, Paul P; Lear, Christopher A; Gunn, Alistair J; Bennet, Laura
Magnesium sulfate is now widely recommended for neuroprotection for preterm birth; however, this has been controversial because there is little evidence that magnesium sulfate is neuroprotective. Preterm fetal sheep (104 days gestation; term is 147 days) were randomly assigned to receive sham occlusion (n = 7), i.v. magnesium sulfate (n = 10) or saline (n = 8) starting 24 h before asphyxia until 24 h after asphyxia. Sheep were killed 72 h after asphyxia. Magnesium sulfate infusion reduced electroencephalograph power and fetal movements before asphyxia. Magnesium sulfate infusion did not affect electroencephalograph power during recovery, but was associated with marked reduction of the post-asphyxial seizure burden (mean ± SD: 34 ± 18 min vs. 107 ± 74 min, P  < 0.05). Magnesium sulfate infusion did not affect subcortical neuronal loss. In the intragyral and periventricular white matter, magnesium sulfate was associated with reduced numbers of all (Olig−2+ve) oligodendrocytes in the intragyral (125 ± 23 vs. 163 ± 38 cells/field) and periventricular white matter (162 ± 39 vs. 209 ± 44 cells/field) compared to saline-treated controls ( P  < 0.05), but no effect on microglial induction or astrogliosis. In conclusion, a clinically comparable dose of magnesium sulfate showed significant anticonvulsant effects after asphyxia in preterm fetal sheep, but did not reduce asphyxia-induced brain injury and exacerbated loss of oligodendrocytes.